Working conditions and compensated sickness absence among nurses and care assistants in Sweden during two decades: a cross-sectional biennial survey study. Issue 11 (10th November 2019) - Marklund, Staffan; Gustafsson, Klas; Aronsson, Gunnar; Leineweber, Constanze; Helgesson, Magnus
Abstract : Objectives: The aims of the study were to trace the patterns of work environment factors and compensated sickness absence (SA) among nurses and care assistants compared with other occupations and to compare SA among exposed and non-exposed nurses and care assistants. Design: A cross-sectional survey on work environment factors based on the biennial Swedish Work Environment Surveys 1991–2013, linked to longitudinal register data on SA 1993–2014. Participants: The study included 98 249 individuals, stratified into nurses and care assistants (n=16 179) and a reference population including all other occupations (n=82 070). Outcome measure: Annual days of compensated SA (>14 days) 3 years after exposure years. Results: Nurses and care assistants had higher SA in 1993–2014 compared with all other occupations, and differences in background factors only partly explained this relationship. For both groups, exposure to physical work factors remained steady, but the number of exposed were 10%–30% higher among nurses and care assistants. Those exposed to heavy physical work and strenuous working postures had in most years significantly higher SA when compared with non-exposed (rate ratio range: 1.4–1.9). Exposure to high job demands increased 10%–25% in 1991–1999 among nurses and care assistants but became more stable in 2001–2013 and high proportions of high job demands coincided with the increase in SA in 1995–1999. Nurses and care assistants exposed to high job demands had for most years significantly higher SA than non-exposed (rate ratio range: 1.5–2.1). Low job control and low support from supervisors elevated SA significantly only for a few years. Conclusions: Exposure to negative work factors among nurses and care assistants was weakly associated with variations in SA, but may be related to their higher level of SA when compared with other occupations. Improved physical and psychosocial working conditions may reduce the elevated SA level in these occupations.